THE RELATIONSHIP BETWEEN WORK-LIFE CONFLICT AND EMPLOYEE PERFORMANCE AT CV SAUDARA JAYA ABADI TAMA, MEDAN - Darwan Tanady; Agus Susanto; Bestadrian Prawiro Theng; Diana Afriani; Edward Harnjo (Bajang Institute, 2022)
Mostly, home conflict just spills over to work area and job stress spills over to home. This calls work-life conflict. As company that specializes in transportation and construction services, CV Saudara Jaya Abadi Tama – Medan is facing problem with its employees. To solve this problem, it is become a priority for company’s management and employees to know what factors that causing work life conflict and understand on how to handle it. In this research, writer uses descriptive research design in collecting, classifying, and analyzing the data. The first method refers to descriptive study which provides explanation of the variable work life conflict and employees’ performance theories. The second method refers to correlative research since the purpose is to find the correlation between independent and dependent variables..